A medical image enhancement method using adaptive thresholding in NSCT domain combined unsharp masking. Issue 3 (20th August 2015) - Liu, Lu; Jia, Zhenhong; Yang, Jie; Kasabov, Nikola; Fellow IEEE
ABSTRACT In the process of medical image formation, the medical image is often interfered by various factors, and it is deteriorated by some new noise that may reduce the quality of the obtained image, which affect the clinical diagnosis seriously. A new medical image enhancement method is proposed in this article. Firstly, the initial medical image is decomposed into the NSCT domain with a low‐frequency sub‐band, and several high‐frequency sub‐bands. Secondly, linear transformation is adopted for the coefficients of the low‐frequency sub‐band. An adaptive thresholding method is used for denoising the coefficients of the high‐frequency sub‐bands. Then, all sub‐bands were reconstructed into spatial domains using the inverse transformation of NSCT. Finally, unsharp masking was used to enhance the details of the reconstructed image. The results of experiment show that the proposed method is superior to other methods in image entropy, EME, and PSNR. © 2015 Wiley Periodicals, Inc. Int J Imaging Syst Technol, 25, 199–205, 2015